Shear bond strength of different adhesive systems to silver diamine fluoride - treated carious dentine - Aimi Amalina Ahmad,; Noor Azlin Yahya,; Yeoh, Oon Take; Adrian, Yap U-Jin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigated the shear bond strength (SBS) of resin composite to silver diamine fluoride (SDF)-treated carious dentine using different adhesive systems and established their failure modes. A total of 75 sound premolars were randomly assigned as follows (n=15); sound dentine with universal adhesive (UA) and etchant (Group A), SDFtreated carious dentine with UA and etchant (Group B), UA without etchant (Group C), glass ionomer (Group D) and alloy (Group E) adhesive systems. Groups B, C, D, and E were subjected to pH cycling to form artificial caries. Resin composite cylinders were bonded to the occlusal surfaces of the treated teeth. The SBS was established using a universal testing machine with shear load of 500N and crosshead speed of 0.5 mm/min. Data for SBS and failure modes were analysed using One-way ANOVA and Pearson Chi-square test, respectively. For SDF-treated carious dentine, Group C presented the highest SBS, followed by Groups B, E, and D. The SBS of Group D and E were significantly lower than Groups A, B, and C. No significant difference in SBS was found between Groups A, B and C. While Group B had significantly fewer adhesive failures, the proportion of mixed failures was statistically insignificant among the different groups. Resin composite cohesive failures were only observed in Group B. In conclusion, UA without etchant is preferred when bonding resin composite to SDF-treated carious dentine. Failure modes were related to the type of adhesive system utilised.